Digital urban modeling and simulation - Arisona, Stefan Müller; Aschwanden, Gideon; Halatsch, Jan; Wonka, Peter (Communications in computer and information science ;, 2012)
This book is thematically positioned at the intersections of Urban Design, Architecture, Civil Engineering and Computer Science, and it has the goal to provide specialists coming from respective fields a multi-angle overview of state-of-the-art work currently being carried out. It addresses both newcomers who wish to obtain more knowledge about this growing area of interest, as well as established researchers and practitioners who want to keep up to date. In terms of organization, the volume starts out with chapters looking at the domain at a wide-angle and then moves focus towards technical viewpoints and approaches -- P. 4 of cover.